Aplikasi Pengolahan Limbah Cair Aliran Horisontal menggunakan Media Pasir Skala Komunal: Horizontal Flow Liquid Waste Treatment Application using Communal Scale Sand Media - Sugeng Nuradji; Andi Respito; Hamsiah Hamsiah (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
Increased human activities in the household resulted in an increase in the amount of liquid waste. The purpose of this PkM activity is to implement a horizontal flow wastewater treatment application using slow sand filter (SSF) media on a communal scale. The method used is a field survey in the village of Guntarano Tanantovea Donggala in February 2022. Interviews with the community and measuring the surface height of the liquid waste distribution system in the yard, taking photos of residential locations regarding the distribution of liquids in the waste distribution system, holding community leaders meetings and outreach. to ensure understanding and roles. as well as being active in the community in making a communal liquid waste distribution system, planning the design of the gravity system for liquid waste distribution, making an understanding with the community and community leaders to determine the time and energy for design development in the horizontal flow technical plan. The results obtained are that the application of wastewater treatment with the role of communal scale sand media can reduce liquid waste pollution and improve proper sanitation for the community. The results of the evaluation of effluent BOD decreased by 77.06%, while COD decreased by 80.82%. It is hoped that this application can be sustainable so that the positive impact felt by the community through this activity is as felt by the community in the village. ABSTRAK Meningkatnya kegiatan manusia dalam rumah tangga mengakibatkan bertambahnya jumlah limbah cair.Tujuan kegiatan PkM ini adalah untuk melakukan penerapan aplikasi pengolahan limbah cair aliran horisontal menggunakan media pasir slow sand filter(SSF) skala komunal. Metodenya survey lapangan desa Guntarano Tanantovea Donggala  bulan Februari 2022. Wawancara dengan masyarakat dan melakukan pengukuran level permukaan sistem penyaluran limbah cair di pekarangan, melakukan pemotretan letak rumah tinggal tentang distribusi sistem penyaluran limbah cair eksisting, melakukan pertemuan tokoh masyarakat serta sosialisasi untuk memastikan kesepahaman dan peran serta aktif masyarakat dalam membuat sistem penyaluran limbah cair sistem komunal, membuat rencana desain sistem penyaluran limbah cair sistem gravitasi, membuat kesepahaman dengan masyarakat dan tokoh masyarakat untuk menentukan waktu dan tenaga untuk pembangunan desain dalam rencana teknis aliran horisontal. Hasil yang diperoleh ialah aplikasi pengolahan limbah cair menggunakan peran media pasir skala komunal dapat mengurangi pencemaran limbah cair dan meningkatkan sanitasi yang layak bagi masyarakat. Hasil evaluasi eflluent BOD menurun 77,06 %, sedangkan COD menurun sebesar 80,82 %. Diharapkan aplikasi ini dapat berkelanjutan sehingga dampak positif yang dirasakan masyarakat lewat kegiatan ini seperti yang dirasakan masyarakat yang ada di Desa.